Clinicopathological Spectrum of EBV and MSI in Gastric Adenocarcinomas - Nethi, Soumya; Kurapati, Samatha; Fonseca, Daphne; Ahmed, Faiq; Krishna Mohan, M C; Kodandapani, Suseela; Rao, T Subramanyeshwar; Challa, Sundaram (Asian Pacific Journal of Cancer Care, 2025)
Introduction: Gastric carcinoma due to Epstein-Barr virus (EBV) and microsatellite instability (MSI) have distinct clinicopathological characteristics that provide specific treatment options. Material and methods: Patients with gastric adenocarcinomas (GC) diagnosed on treatment-naïve endoscopic biopsy/resection specimens during 19 months were included. The samples were subjected to EBER-ISH and mismatch repair (MMR) protein status by immunohistochemistry and the demographic features, endoscopy/gross features and histologic type were correlated between EBV positive vs negative and MMR-deficient vs proficient groups. Results: EBV was positive in 3.1% (3/97) of GC. Two of the three patients were males with tumor in the proximal part of the stomach showing poorly cohesive NOS (WHO)/diffuse (Lauren) histology. All the three patients had thickening of the gastric wall and lymph node involvement on CECT and received palliative chemotherapy. MMR-d GC constituted 8% (6/75) of GC. There was female predominance with median age of 53 years. All were in the body of the stomach showing3 each of poorly cohesive (NOS) and tubular adenocarcinoma (WHO)/ intestinal (2), indeterminate (1) and diffuse (3) (Lauren). The loss of MMR expression was seen as heterodimers: MLH1+PMS2 in 04 (66.67%) and MSH2+MSH6 in 01 (16.67%) and isolated loss of PMS2 in 01 (16.67%). Patients received immunotherapy/ palliative chemotherapy. EBV positive and MMR-d GC were mutually exclusive. There was no statistically significant difference in EBV positive vs negative or MMR-d vs proficient groups in clinicopathological features. Conclusion: Routine testing for EBV by EBER-ISH and MMR by IHC can identify molecularly distinct gastric carcinoma for therapy and prognosis.